The Effect of Product Knowledge, Product Diversity, and Store Atmosphereon Consumer Purchase Decisions at Medan Abadi Store - Manik, Desma Erica Maryati; Gultom, Pesta; Angga, Ivone (Dinasti Publisher, 2025)
This study aims to test and analyze the influence of product knowledge, product diversity, and store atmosphere on consumer purchasing decisions at Toko Medan Abadi, a furniture store in Medan City. The decline in sales that has occurred in recent years is the background to the importance of this study. Quantitative data were collected through questionnaires distributed to 150 respondents selected using the accidental sampling technique. The data analysis technique used was multiple linear regression. The results of the study showed that partially, product knowledge, product diversity, and store atmosphere had a positive and significant effect on consumer purchasing decisions. In addition, simultaneously, the three independent variables also had a significant effect on purchasing decisions. This study suggests that Toko Medan Abadi improve employee product mastery, increase product variety, and improve the quality of store atmosphere in order to increase consumer purchasing decisions and support store sales growth.